2002
DOI: 10.1177/154405910208100403
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adenosine-receptor-enhanced iNOS mRNA Expression by Gingival Epithelial Cells

Abstract: A series of reports has revealed that adenosine has a plethora of biological actions toward a large variety of cells. In this study, we investigated the influence of adenosine receptor activation on iNOS mRNA expression in human gingival epithelial cells (HGEC) and SV-40-transformed HGEC. HGEC expressed adenosine receptor subtypes A1, A2a, and A2b, but not A3 mRNA. Ligation of adenosine receptors by a receptor agonist, 2-chloroadenosine (2CADO), enhanced iNOS mRNA expression by both HGEC and transformed HGEC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The effect of the CaR on iNOS is not a nonspecific event caused by activation of any GPCR, since activation of a functional G␣ q-11 -coupled purinergic receptor in these cells by ADP␤S (a nondegradable form of ADP) failed to alter iNOS expression in the H-500 cells. Activation of ADP receptors (like the CaR, a GPCR coupled to G␣ q-11 ) has been reported to upregulate the level of iNOS mRNA in human gingival epithelial cells (22). In the same cells, additional studies showed that IL-15 enhanced iNOS expression at both the mRNA and protein levels, similar to our study (39).…”
Section: Discussionsupporting
confidence: 87%
“…The effect of the CaR on iNOS is not a nonspecific event caused by activation of any GPCR, since activation of a functional G␣ q-11 -coupled purinergic receptor in these cells by ADP␤S (a nondegradable form of ADP) failed to alter iNOS expression in the H-500 cells. Activation of ADP receptors (like the CaR, a GPCR coupled to G␣ q-11 ) has been reported to upregulate the level of iNOS mRNA in human gingival epithelial cells (22). In the same cells, additional studies showed that IL-15 enhanced iNOS expression at both the mRNA and protein levels, similar to our study (39).…”
Section: Discussionsupporting
confidence: 87%
“…Simian virus‐40 antigen‐mediated, immortalized gingival epithelial cell lines, epi 4 and OBA‐9 , were maintained in Humedia‐KG2 medium (Kurabo, Osaka, Japan) containing 0.5 μg/mL hydrocortisone, 10 μg/mL insulin, 0.4% v/v bovine pituitary extract, 0.1 ng/mL human epidermal growth factor, 50 μg/mL gentamycin and 50 ng/mL amphotericin B. For analysis, cells were cultured in Humedia‐KB2 (Kurabo) medium containing 50 μg/mL gentamycin and 50 ng/mL amphotericin B.…”
Section: Methodsmentioning
confidence: 99%
“…The human gingival epithelial cell line epi 4 (18) was used in this study. The cells were maintained in Humedia‐KG2 (Kurabo, Osaka, Japan) supplemented with 0.5 μg ml −1 of hydrocortisone, 10 μg ml −1 of insulin, 0.4% (v/v) bovine pituitary extract, 0.1 ng ml ‐1 of human epidermal growth factor, 50 μg ml −1 of gentamicin, and 50 ng ml −1 of amphotericin B (all from Kurabo).…”
Section: Methodsmentioning
confidence: 99%